Implementasi Metode DevOps Approach dalam Pengembangan Sistem Pengarsipan Surat RENMIN SDM Polda Bengkulu - khairullah; Apridiansyah, Yovi; Pahrizal; sungkowo, belo (Jurnal Sistem Informasi dan E-Bisnis, 2025)
This study discusses the development of the Bengkulu Regional Police Human Resources RENMIN Letter Filing System, utilizing the DevOps approach, which integrates development and operations processes continuously. The objective is to enhance release speed, system quality, and the efficiency of digital document management. Evaluation was conducted using the User Acceptance Testing (UAT) method on 50 respondents, covering five key indicators: system functionality, ease of use, access speed, system security, and compliance with work procedures. The test results showed a high success rate, at 96%, 94%, 92%, 97%, and 95%, respectively, with an average success rate of 94.8%. These findings prove that the implementation of DevOps can provide a responsive, reliable, and user-friendly system in a police environment. Keywords— DevOps, RENMIN SDM, Document Management, Police Administration